Structural auto- and allograft glenoid bone grafting in reverse shoulder arthroplasty - Retrospective radiological analysis of 38 cases - Lehtimäki, Kaisa; Holstila, Milja; Mäkelä, Keijo; Kukkonen, Juha; Tirkkonen, Kari; Harjula, Jenni; Kauko, Tommi; Äärimaa, Ville (Indian Orthopaedic Research Group, 2025)
Background: A structural glenoid bone graft may be utilized in conjuction with reverse shoulder arthroplasty (RSA) in order to address native bone deficiency and/or lateralize the glenoid. The longevity of this type of construct is of potential concern especially with allograft bone grafting. We wanted to study the radiographic construct survival in primary and revision RSA with structural glenoid auto- and allograft bone grafting.
Methods: We retrospectively identified all patients who had undergone RSA, with an encompassing structural bone graft under the metaglene bearing at Turku University Hospital between 2014 and 2019. All patients were called for follow-up and evaluated radiographically and clinically. Shoulders were divided into auto- and allograft groups and radiographic bone graft incorporation and component survival were used as primary outcome measures and between group differences were statistically analyzed.
Results: There were 38 shoulders/34 patients (out of 56) with a mean follow-up of 34 months. The mean age of patients at time of surgery was 69 years (SD 11). 26 auto- and 12 allografts were used at index surgery. At follow-up the bone graft was fully incorporated, partially incorporated and fully resorbed in 44 %, 50 % and 6 % of cases respectively. There was no statistically significant difference in bone graft incorporation between the groups and none of the prosthesis components showed radiographic signs of loosening.
Conclusions: Glenoid bone grafting in conjunction with RSA is a safe and reliable method to restore the glenoid bone stock and secure the construct in short term follow-up. There may be no significant difference in component survival between auto- and allograft bone grafting techniques. Longer-term follow-up is needed to assess the final outcome with regard to these techniques.